Development of a multicriteria model for making decisions on the location of solid waste landfills - Kuznichenko, Svitlana; Kovalenko, Ludmila; Buchynska, Iryna; Gunchenko, Yurii (Eastern-European Journal of Enterprise Technologies, 2018)
We have developed a structure of the multi-criteria model of decision making related to determine optimal sites for the location of solid waste landfills (using the south of Odessa oblast as an example). A special feature of the model is the integration of GIS and the multi-criteria methods of decision-making. Based on the created raster criteria maps in the GIS geodatabase and expert estimation of the significance of criteria, we ranked alternatives according to the degree of suitability. A multilevel hierarchical decision-making structure includes three groups of criteria: environmental, physical, and socio-economic; it takes into consideration the state building requirements to the construction of SW polygons. Such an approach provides for the acceptability of results of the analysis by most stakeholders. The simulation is performed for the three scenarios that imply the aggregation of layers of criteria into a combined map of suitability using Boolean logic, fuzzy logic, and a combination of methods of weighted overlay and a fuzzy analysis of hierarchies. To account for the uncertainty of original information and subjectivity in expert assessments, we employed an apparatus of fuzzy logic. Piecewise-linear membership functions of the fuzzy set are proposed for the standardization of criteria. We calculated weights of criteria using a modified method of the analysis of hierarchies, in which we used linguistic variables represented by triangular fuzzy numbers to perform the paired comparison of criteria significance. The results of the simulation show that the use of operations of a fuzzy intersection or a fuzzy combination in order to aggregate a combined suitability map can lead to errors related to the underestimation or overestimation of alternatives. The most acceptable method is a weighted linear combination, or the operation of fuzzy geometric averaging, in cases when it is difficult or impossible to determine the weight of criteria.